2019
DOI: 10.3382/ps/pey358
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble substances of wheat: a potential preventer of aflatoxin B1-induced liver damage in broilers

Abstract: Aflatoxin B1 (AFB1) is very harmful for broiler production and public health. The water-soluble castoff in gluten production, i.e., the water-soluble substances of wheat (WSW) that contains 14% pentosan has positive effect on animal nutrient absorption, immunity, and antioxidation. Our study aims to investigate the preventive effects of WSW against AFB1-induced broiler liver injury. One day-old Arbor Acres broilers were randomly separated to 4 groups and were, respectively, fed with control diet, diet with 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…Moreover, the adsorbent supplementation improved BW, ADG, and ADFI in starter phase compared with AFB-contaminated diets and eliminated the growth reduction to control diets. The results agreed with previous studies, which also demonstrated that the activated carbon or HSCAS improved ADG and ADFI of the AFB-treated broilers [9,12,29,30].…”
Section: Growth Performancesupporting
confidence: 92%
“…Moreover, the adsorbent supplementation improved BW, ADG, and ADFI in starter phase compared with AFB-contaminated diets and eliminated the growth reduction to control diets. The results agreed with previous studies, which also demonstrated that the activated carbon or HSCAS improved ADG and ADFI of the AFB-treated broilers [9,12,29,30].…”
Section: Growth Performancesupporting
confidence: 92%
“…The hepatic accumulation of AFB 1 in broilers was 0.17 μg/kg after they consumed feed containing 1000 μg AFB 1 /kg in the pure crystal form for seven weeks [52], whereas a similar concentration of AFB 1 produced by A. flavus (NRRL 3357) led to the deposition of 0.33 μg AFB 1 /kg in chicken livers after feeding the contaminated diet for 28 days [30]. In addition, increasing the level of AFB 1 from a pure source five-fold (5000 μg AFB 1 /kg) for 18 days led to the accumulation of less AFB 1 in the liver (0.11 μg/kg) [53] compared with the levels detected by Denli et al [52] (0.17 μg AFB 1 /kg) and Rajput et al (0.33 μg AFB 1 /kg) [30], thereby indicating that the concentration of AFB 1 is not the only major factor that determines the effect of AFB 1 and its accumulation in edible poultry parts; the fungal strain producing the toxin may, instead, be the main factor. In addition to the risks associated with the detection of AFB 1 in the edible parts of poultry, the presence of malondialdehyde (MDA) may be more hazardous than AFB 1 to human health.…”
Section: Effects Of Aflatoxin B1 Produced By Aspergillus Flavus Anmentioning
confidence: 99%
“…Abnormal liver size may be associated with liver malfunctions. AFB 1 can cause imbalanced lipid metabolism, promoting lipid deposition in the enlarged liver [107,108], repress the activity of antioxidant enzymes and anti-inflammatory cytokines, enhance lipid peroxidation and pro-inflammatory cytokines, and increase hepatocyte apoptosis [53,109,110,111,112,113]. The usual deleterious effects of AFB 1 on hepatocytes result in high concentrations of aspartate aminotransferase and alanine aminotransferase in poultry blood after feeding diets containing AFB 1 [37,50,71,81,114].…”
Section: Effects Of Aflatoxin B1 Produced By Aspergillus Flavus Anmentioning
confidence: 99%
“…This can result in oxidative stress owing to an imbalance between limited antioxidant defenses and the excessive formation of ROS, resulting in the damage of biological molecules including lipids, proteins, and DNA in cellular systems [34,35]. In support of this hypothesis, several studies have demonstrated the potential for antioxidants to lower the risk of hepatotoxicity caused by exposure to the AF [29,[36][37][38][39]. Moreover, many studies have reported the pivotal role of oxidative stress induced by AF in eliciting programmed cell death or apoptosis through mitochondrial signaling pathways [25,[40][41][42].…”
Section: Discussionmentioning
confidence: 96%